Kerala: Radical Reform As Development in an Indian State. 2nd Edition. - Franke, Richard W.; Chasin, Barbara H. (Institute for Food and Development Policy, 1994)
Kerala, a state in southwestern India, has implemented radical reform as a development strategy. As a result, Kerala now has some of the Third World's highest levels of health, education, and social justice. Originally published in 1989, this book traces the role that movements of social justice played in Kerala's successful struggle to redistribute wealth and power. A 21-page introduction updates the earlier edition. This book underlines the following positive lessons that the Kerala experience offers to developing countries: Radical reforms deliver benefits to the poor even when per capita incomes remain low. Popular movements and militant progressive organizations with dedicated leaders are necessary to initiate and sustain reform. Despite their other benefits, radical reforms cannot necessarily create employment or raise per capita income. Local reformers are restricted by national politics. Public distribution of food is a highly effective policy in poor agrarian economies. Devoting significant resources to public health can bring about low infant mortality, high life expectancy, and low birth rates even when incomes are low. Widespread literacy and educational opportunities can help create a more just and open social order. Meaningful land reform can reduce inequalities and give resources to the poor. Wage and working-condition laws can help effect more equitable resource distribution even in a poor economy. Greater socioeconomic equality can lead to lower levels of violence and a healthier social and political environment. Women can benefit from radical reforms not aimed at them, but special attention must eventually be given to their needs. Progressive forces, including Communist parties, can play a major positive role in benefiting very poor Third World citizens. Radical reforms can shield the poor against recessions. Contains over 200 references.